Production and application of steel slag coarse aggregate in asphalt mixture. Issue 1 (7th June 2017) - Zhao, Meiling; Wu, Shaopeng; Chen, Zongwu; Li, Chao
Abstract : Natural resource shortages and environmental issues have advanced the applications of industrial waste in road construction. Steel slag is a typical industrial waste. Its use in asphalt pavement is a hot topic. The lack of a production technique for high-quality steel slag aggregate has limited the wide use of steel slag in asphalt pavement in China. The primary objective of this research is to establish an advanced technique for steel slag coarse aggregate production. A modified production process consisting of a combined crushing, screening and cleaning technique is proposed. The quality of the steel slag coarse aggregate produced by the modified method and the performance of the asphalt mixture containing this steel slag coarse aggregate have been examined. The results show that the proposed production method significantly enhances the angularity and size specification stability of steel slag coarse aggregate. Asphalt mixtures with steel slag coarse aggregate shows satisfactory crack resistance and high-temperature deformation resistance.